Unveiling the Bovine Epimural Microbiota Composition and Putative Function - Cátia Pacífico; Renée Maxine Petri; Sara Ricci; Elsayed Mickdam; Stefanie Urimare Wetzels; Viktoria Neubauer; Qendrim Zebeli (Microorganisms, 2021)
Numerous studies have used the 16S rRNA gene target in an attempt to characterize the structure and composition of the epimural microbiota in cattle. However, comparisons between studies are challenging, as the results show large variations associated with experimental protocols and bioinformatics methodologies. Here, we present a meta-analysis of the rumen epimural microbiota from 11 publicly available amplicon studies to assess key technical and biological sources of variation between experiments. Using the QIIME2 pipeline, 332 rumen epithelial microbiota samples were analyzed to investigate community structure, composition, and functional potential. Despite having a significant impact on microbial abundance, country of origin, farm, hypervariable region, primer set, animal variability, and biopsy location did not obscure the identification of a core microbiota. The bacterial genera Campylobacter, Christensenellaceae R-7 group, Defluviitaleaceae UCG-011, Lachnospiraceae UCG-010, Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-010, Ruminococcaceae UCG-014, Succiniclasticum, Desulfobulbus, and Comamonas spp. were found in nearly all epithelium samples (>90%). Predictive analysis (PICRUSt) was used to assess the potential functions of the epithelial microbiota. Regularized canonical correlation analysis identified several pathways associated with the biosynthesis of precursor metabolites in Campylobacter, Comamonas, Desulfobulbus, and Ruminococcaceae NK4A214, highlighting key metabolic functions of these microbes within the epithelium.